CHINA AND ITS INTERESTS IN LATIN AMERICA - Naranjo-Navas, Bryan J.; Naranjo-Navas, Christian P. (KAIRÓS, revista de ciencias económicas, jurídicas y administrativas, 2020)
It is a reflection article based on a bibliographic review. Its objective is to analyze the Chinese political and economic interest in Latin America, especially, to examine Chinese investments in the strategic sectors in Venezuela, Brazil, Argentina, and Ecuador. The article reaches three conclusions that help to understand this influence: first, the influence of China was possible by the political withdrawal of the governments of the United States; second, China's growing need to supply its raw material industries; and third, the generation of debtors that would be linked to China for many years, in some cases, the payments were scheduled to finish in a couple of decades. Within these elements, China's influence over the region has developed, increased, and strengthened.